SeniorTec: Senior Tutorial Program to Teach Technologies to Students. Issue 4 (2nd October 2019) - Gerardo, Filomena; Rodrigues, Bárbara; Marques, Sibila; Cunha, Cátia; Mendonça, Joana; Pinto, Élia; Grilo, Margarida
ABSTRACT: The SeniorTec program was carried out in the framework of the European project Cordon Gris, its objective was to promote intergenerational relationships. The activity was hosted by the old persons who participate in the European project Cordon Gris and was attended by university students from Higher School of Health of Alcoitão and ISCTE-University Institute of Lisbon. Learning sessions were delivered in this action: a Nutrition Workshop and a Financial Education Workshop. After this, an intergenerational contact session took place by using the Cordon Gris app. The SeniorTec program could promote a more positive image of aging and deconstruct negative stereotypes. Valuing older people in technology can act as a powerful vehicle to improve images of aging and to encourage intergenerational contact